Synergistic Anti-Biofilm Activity of Klanceng Honey and Probiotics against Candida albicans - Setiawan, Budhi; Masfufatun, Masfufatun; Tjandra, Lusiani; Ishartadiati, Kartika (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Candida albicans is a common cause of fungal infections, especially in hospitals. Biofilm formation by this fungus is a significant problem as it leads to increased drug resistance and complications in treatment. The biofilm's extracellular matrix protects the fungal cells, making it difficult for antifungal drugs to penetrate and clear the infection. Aim: This study investigates the potential of honey and probiotic formulations to inhibit the biofilm matrix formation in Candida albicans. Result: Klanceng honey showed the strongest inhibition of Candida albicans biofilm formation, reducing it by 89.39% (OD = 0.34 ± 0.10), compared to yogurt (29.43%, OD = 2.25 ± 0.16) and Yakult (67.95%, OD = 1.02 ± 0.25) (p < 0.05). When mixed with yogurt in a 5:1:2 ratio (honey:yogurt: water), Klanceng honey reduced biofilm formation by 84.92% (OD = 0.50 ± 0.12). Manuka and Melifera honey in the same ratio also showed strong inhibition, reducing biofilm formation by 77.84% (OD = 0.73 ± 0.08) and 90.52% (OD = 0.31 ± 0.07), respectively. This performance exceeded fluconazole’s, which achieved a 65.52% reduction (OD = 1.14 ± 0.02). For all three honey types, the 4:1:3 and 2:1:5 ratios (honey:Yakult: water) were more effective, with reductions of up to 80.96% for Melifera and 75.64% for Klanceng (p < 0.05). Conclusion: This research suggests that honey and probiotic formulations hold promise as natural alternatives in combating Candida albicans infections. The study found that the ratio of honey to probiotics in the formulations significantly influenced their effectiveness.